Search 75,671 tutors
FIND TUTORS
Ask a question
0 0

work out the problem to understand how to get to the answer

Tutors, please sign in to answer this question.

2 Answers

You can also look at this equation as the multiplication of two fractions:

1. 3b8 * 49p5 / 7p3 * 9b is the same as (3b8/9b) * (49p5/7p3)

2. Now lets simplify the fractions before multiplying them together:

a. 3b8/9b

= b8/3b 

= b8-1/3

= b7/3

b. 49p5/7p3

= 7p5/p3

= 7p5-3

= 7p2


3. Lastly complete the multiplication --> b7/3 * 7pwhich is 7b7p2/3

 

First, let's use the order of operations (PEMDAS) to make the expression easier to look at:

(3b8) * (49p5) / (7p3) * (9b)

Now we have only multiplication and division; take care of multiplication first:

(147b8p5) / (63bp3)           In this step, we can't yet combine like terms.

And now dividing these terms leaves us with:

7/3b7p2        Here we must remember that dividing terms with the same base means subtracting their exponents (e.g., b8 / b = b8-1 = b7).

Hope this helps.